Italian Expert Opinion on Chronic Hand Eczema: from Guidelines to Clinical Practice - Luca Stingeni; Maria Concetta Fargnoli; Fabrizio Guarneri; Anna Balato; Monica Corazza; Anna Belloni Fortina; Piergiacomo Calzavara Pinton; Antonio Costanzo; Silvia Mariel Ferrucci; Luigi Naldi; Giovanni Pellacani; Ketty Peris; et al. (Dermatology and Therapy)
Abstract Introduction Chronic hand eczema (CHE) is an inflammatory skin condition characterized by different pathomechanisms, clinical presentations, and prognoses. Treatment is often challenging because of limited approved drugs, and severe CHE is associated with reduced quality of life (QoL) and poor overall health measures in terms of psychological, functional, and occupational challenges. This study aims to describe the real-life management practices of Italian dermatologists who frequently treat patients with CHE, compare these practices with existing guidelines, and propose practical clinical recommendations for the management of these patients. Methods An 11-question survey was administered to 14 participating dermatologists to gather their insights on the diagnosis, treatment, and management of CHE. Moreover, a comprehensive literature search was conducted over the previous 10 years as a starting point for discussion among experts. Results CHE was the reason for 6.9% of dermatological consultations by the 14 experts. Median time to CHE diagnosis was 12 (range: 2–24) months. Fissuring and itching (85.7% for both) were the most frequently reported signs and symptoms of CHE. The survey highlighted the need for long-term treatment that is effective and well tolerated, with experts emphasizing the importance of improving disease awareness among physicians and patients. Practical clinical approaches were proposed, emphasizing the significance of a thorough medical history and identification of symptoms in the management of CHE. Experts advocated for specifically developed CHE treatment approaches, concentrating on alleviating symptoms and signs, minimizing adverse events/safety issues, enhancing the QoL of patients, and long-term disease control. Findings from this survey were further discussed and compared to recommendations of the available guidelines for the management of CHE. Conclusions Managing CHE requires a comprehensive approach that considers both objective clinical factors and subjective patient expectations. Experts emphasized the need for effective and well-tolerated long-term therapies, improved disease awareness, and communication among physicians and patients.